Covid-19 2.0. Derecho internacional y protección del derecho a la salud en el ciberespacio: una visión desde Ecuador - Martín Tamayo Serrano; Víctor Calderón Merino (Ius Humani. Jornal do direito, 2020)
The purpose of this article is to explore the opportunity offered by the Covid-19 crisis in Ecuador to interpret international human rights law and international humanitarian law to protect the right to health, and also health-care systems in cyberspace. Through a descriptive methodology that allows a comprehensive analysis of the issue from a legal point of view, this article: synthesizes the main international debates on the scope of the protection of the right to health under the international human rights law against cyber threats; studies the protection that international humanitarian law provides to citizens and health-care systems; and examines Ecuador’s situation, as a country facing several challenges in the application of the necessary policies to ensure the protection of the right to health and health-care systems. The article concludes that the legal developments in both sectors have not managed to establish means of protection which are acceptable and effective, with clear obligations for States in cyberspace to protect individuals and health-care systems. Additionally, it argues that the gaps in international law regarding the protection of health in cyberspace are exacerbated in Ecuador by a discursive dissonance between foreign and domestic policy, with an impact on the protection of the right to health.